Respuesta :

Answer:

(3, 4)

Step-by-step explanation:

Using elimination method:

3x + 8y = 41

-3(x + 2y = 11)

-3x -6y = -33

2y = 8

y = 4

x = 3 (plug y back into the equation)

(3, 4)

Answer:

[tex]3x + 8y = 41 - - (1) \\ x + 2y = 11 - - (2) \\ (2) \: x + 2y = 11 \\ x = 11 - 2y - (3) \\ (3)in(1) is \: \: 3(11 - 2y) - 8y = 41 \\ 33 - 6y + 8y = 41 \\ 33 + 2y = 41 \\ 2y = 41 - 33 \\ 2y = 8 \\ y = \frac{8}{2} \\ y = 4 \\ y = 4 \: in \: (2) \: is \: x + 2(4) = 11 \\ x + 8 = 11 \\ x = 11 - 8 \\ x = 3[/tex]